Natural history of nonhuman primates after conjunctival exposure to Ebola virus - Cross, Robert W.; Prasad, Abhishek N.; Woolsey, Courtney B.; Agans, Krystle N.; Borisevich, Viktoriya; Dobias, Natalie S.; Comer, Jason E.; Deer, Daniel J.; Geisbert, Joan B.; Rasmussen, Angela L.; Lipkin, Walter Ian; Fenton, Karla A.; et al. (Scientific reports, 2023)
Transmission of Ebola virus (EBOV) primarily occurs via contact exposure of mucosal surfaces with infected body fluids. Historically, nonhuman primate (NHP) challenge studies have employed intramuscular (i.m.) or small particle aerosol exposure, which are largely lethal routes of infection, but mimic worst-case scenarios such as a needlestick or intentional release, respectively. When exposed by more likely routes of natural infection, limited NHP studies have shown delayed onset of disease and reduced mortality. Here, we performed a series of systematic natural history studies in cynomolgus macaques with a range of conjunctival exposure doses. Challenge with 10,000 plaque forming units (PFU) of EBOV was uniformly lethal, whereas 5/6 subjects survived lower dose challenges (100 or 500 PFU). Conjunctival challenge resulted in a protracted time-to death compared to i.m. Asymptomatic infection was observed in survivors with limited detection of EBOV replication. Inconsistent seropositivity in survivors may suggest physical or natural immunological barriers are sufficient to prevent widespread viral dissemination.